Patterns of Chemotherapy Use in a U.S.‐Based Cohort of Patients with Metastatic Pancreatic Cancer. (5th May 2017) - Abrams, Thomas A.; Meyer, Gary; Meyerhardt, Jeffrey A.; Wolpin, Brian M.; Schrag, Deborah; Fuchs, Charles S.
Abstract : Purpose: Few population studies have examined patterns of systemic therapy administration in metastatic pancreatic cancer (MPC) or the predictors associated with specific treatment choices. Patients and Methods: We assessed 4, 011 consecutive MPC patients who received chemotherapy between January 2005 and December 2015 at academic, private, and community‐based oncology practices subscribing to a U.S.‐wide chemotherapy order entry system capturing disease, patient, provider, and treatment data. Multivariate analyses of these prospectively recorded characteristics identified significant predictors of specific therapeutic choices. Results: Overall, 100 different regimens were used in first‐line treatment of MPC. First‐line gemcitabine monotherapy usage fell steadily from 72% in 2006 to 16% in 2015. This steep decline mirrored increases in first‐line usage of both 5 fluorouracil, leucovorin, irinotecan and oxaliplatin (FOLFIRINOX) and gemcitabine + nab‐paclitaxel. Younger male patients were more likely to receive FOLFIRINOX as first‐line treatment, whereas patients treated at community practices and by oncologists with lower MPC patient volume were more likely to receive gemcitabine plus nab‐paclitaxel (all p ≤ .05). Among all patients receiving first‐line chemotherapy for MPC, 49% went on to receive second‐line therapy and 19% received third‐line therapy; administration of second‐ and third‐line therapies increased steadily over the time course of follow‐up. Younger patients and those treated by oncologists with higher MPC patient volume were more likely to receive second‐ and third‐line therapies. Conclusion: This population‐based study provides insight into treatment patterns of MPC in the U.S. Usage patterns varied greatly according to patient and provider characteristics. Abstract : The aim of this study was to understand factors influencing treatment decisions for patients with metastatic pancreatic cancer. Data from a nationwide, commercially available chemotherapy order entry system, including tumor stage, disease status, and treatment indication, was analyzed. Temporal trends were identified for prescribing patterns across the continuum of metastatic pancreatic cancer therapy, as well as patient and provider characteristics influencing treatment selection across multiple lines of therapy.